Conceptual Study of TrividhChikitsa Karma in Shalya Tantra– A Review: LifeScience-Surgery - Mavale, Dr. Abhishek; Dasar , Dr. Devyani (International Journal of Life Science and Pharma Research, 2023)
Ayurveda focuses on integrating and balancing the body, mind, and spirit rather than on specific illnesses. Shalyatantrais associated with the sage-physician Sushruta. Given the early stage of human history and the absence of any supporting body ofknowledge before his era, his concepts of anatomy, pathophysiology, and therapeutic approaches were incomparable. AcharyaSushruta has described the entire course of medical treatment in connection with a disease, which may be grouped under thesesubheadings as the initial steps (Purva Karma), the main therapeutical or surgical appliances (Pradhana-Karma), and the follow-upsteps (Paschat Karma) regardless of the surgical procedure. Surgery comprises the main action (operation) but also the care ofthe patient before and after the technique. Acharya Sushrut, regarded as the father of surgery in Ayurveda, chose these threeKarma solely and only for the benefit of patients who undergo any surgical procedure. In this article, we compare ancient andcontemporary surgical practices, contrasting prior articles or research that solely focused on particular Karma, upkramas, andspecific topics.In our article, we contrasted several old and contemporary strategies in a simple way for students to grasp.Thisarticle compares several parts of trividha karma with contemporary surgical techniques, demonstrating the relevance of ouracharyas’ siddhanta even today.